2017
DOI: 10.1177/0022034516688659
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Enamel Regeneration Mediated by Leucine-Rich Amelogenin Peptide

Abstract: We report here a novel biomimetic approach to the regeneration of human enamel. The approach combines the use of inorganic pyrophosphate (PP) to control the onset and rate of enamel regeneration and the use of leucine-rich amelogenin peptide (LRAP), a nonphosphorylated 56-amino acid alternative splice product of amelogenin, to regulate the shape and orientation of growing enamel crystals. This study builds on our previous findings that show LRAP can effectively guide the formation of ordered arrays of needle-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 37 publications
1
48
0
2
Order By: Relevance
“…In vitro studies have shown treatment of enamel lesions with leucine-rich amelogenin peptide reduced lesion depth and allowed biomimetic reconstruction of enamel by promoting linear growth of mature enamel crystals along the c-axis [Bagheri et al, 2015;Mukherjee et al, 2016;Shafiei et al, 2015]. The addition of mineralization inhibitors such as inorganic pyrophosphate or matrix metalloproteinase to synthetic amelogenin assemblies was able to better regulate size, shape, and orientation of a strongly adherent new mineral layer, while preventing undesirable protein occlusion within newly formed crystals [Kwak et al, 2017;Prajapati et al, 2018].…”
Section: Amelogeninmentioning
confidence: 99%
“…In vitro studies have shown treatment of enamel lesions with leucine-rich amelogenin peptide reduced lesion depth and allowed biomimetic reconstruction of enamel by promoting linear growth of mature enamel crystals along the c-axis [Bagheri et al, 2015;Mukherjee et al, 2016;Shafiei et al, 2015]. The addition of mineralization inhibitors such as inorganic pyrophosphate or matrix metalloproteinase to synthetic amelogenin assemblies was able to better regulate size, shape, and orientation of a strongly adherent new mineral layer, while preventing undesirable protein occlusion within newly formed crystals [Kwak et al, 2017;Prajapati et al, 2018].…”
Section: Amelogeninmentioning
confidence: 99%
“…Although not fully understood, the biomimetic approach has utilized amelogenin to regenerate enamel-like materials on teeth in gentle and close to physiological conditions [6]. Full-length amelogenin [7], leucine-rich amelogenin peptide (LRAP) [8] and other amelogenin-derived peptides [9] have all been tested and proved to have great potential in dentistry or biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…82,83 Amelogenin düşük maliyetli ve daha güvenli bir alternatifi olan 56 amino asitten oluşan lösin bakımından zengin amelogenin peptidinin lezyon derinliğini düşürdüğünü ve c-ekseni boyunca olgun mine kristallerinin doğrusal büyümesini teşvik ederek mine biyomimetik rekonstrüksiyonunu sağladığı gösterilmiştir. 84,85 İnorganik pirofosfat veya matris metaloproteinaz gibi mineralizasyon in-hibitörleri eklenen sentetik amelogeninlerin yeni mineral katmanının boyutunu, şeklini ve oryantasyonunu daha iyi düzenleyebildiği bulgulanmıştır. 85 Amelogenin elde edilmesi ve depolanması zordur ve amelogenin ile teşvik edilen mine tabakasının büyümesi uzun süre alır, bu nedenle klinik kullanım için uygun değildir.…”
Section: Amelogeninunclassified
“…84,85 İnorganik pirofosfat veya matris metaloproteinaz gibi mineralizasyon in-hibitörleri eklenen sentetik amelogeninlerin yeni mineral katmanının boyutunu, şeklini ve oryantasyonunu daha iyi düzenleyebildiği bulgulanmıştır. 85 Amelogenin elde edilmesi ve depolanması zordur ve amelogenin ile teşvik edilen mine tabakasının büyümesi uzun süre alır, bu nedenle klinik kullanım için uygun değildir. Ayrıca, amelogeninin vitro olarak apatit çekirdeklenmesini arttırdığı bulgulanmış olsa da, benzer biyomineralizasyonun in vivo olarak gerçekleştiğine dair doğrudan bir kanıt yoktur.…”
Section: Amelogeninunclassified